Debtor Communicative Strategies Analysis in “Confession of a Shopaholic” by S. Kinsella - Shabelnyk, K.; Bober, N. (Studia Philologica, 2022)
The anthropocentric nature of modern linguistics has led to the need to study not only the regularities of human communication but also the ways of their use in various communicative situations. The main communicative strategies and the specifics of the DEBTOR's language means were characterized in this article. The article discusses the effectiveness of the chosen tactics in the communication process. The paper readdresses the phenomenon of a communicative strategy and tackles the ways the chosen strategies control the communicative process aimed at achieving communicative goals and the selection of speech techniques that allow achieving the set goals in a specific situation. Special attention is paid to the analysis of behavioral activities and verbal means used by a DEBTOR in Sophie Kinsella's novel "Confessions of a Shopaholic". The paper argues that DEBTOR’s communicative strategies depend on the specific situation and psychological characteristics of the addressee. The material of the study is presented in the form of the types of speech strategies in the framework of the communication process in Sophie Kinsella's novel "Confessions of a Shopaholic". The objects of analysis are communicative strategies as a set of speech actions. The relevance of the study is determined by the need to establish an inventory of communicative strategies for successful communication as the main component of the debtor, the importance of identifying the most productive strategy, and the formation of positive behavior during communication. The article highlights the following strategies that are productive in DEBTOR’S speech: Termination, Topic Control, Topic Shifting, and Repair Strategy. Such strategies as Nomination, Restriction, and Turn Taking belong to the least productive ones. The result of the study is the matrix of 7 types of communicative strategies from the most frequent to the least used in DEBTOR's speech. From the perspective of research, there may be the establishment of communicative strategies in political discourse, politicians' speeches, and thematic webinars to discuss various aspects of the problem.